P163 HIV care and treatment services for female sex workers: utilisation of and satisfaction with the services in kampala, uganda. (14th July 2019) - Namale, Gertrude; Ssali, Agnes; Kamacooko, Onesmus; Bagiire, Daniel; Mayanja, Yunia; Nalukenge, Winfred; Seeley, Janet
Abstract : Background: We estimated the prevalence and factors associated with utilisation of HIV services among FSW in Kampala, Uganda. Methods: Between October 2017 to January 2018, we conducted a cross sectional study among FSW aged 18+ years at a research clinic. The women were enrolled through their routine three monthly visits. At each visit, women received a comprehensive HIV prevention, care and treatment package, peer-led -health education sessions, psycho-social support, sexually transmitted infections (STIs) screening and treatment, general health care and reproductive health services. We defined utilisation as clinic attendance for services by FSW at least once within the last six months. Data on socio-demographic characteristics, clinic attendance, HIV sero-status, sexual behaviour, illicit drug and alcohol use were collected. We used log binomial model to identify factors associated with utilisation of clinic services. Results: Eight hundred and seventy four women were included in the analysis, mean age was 32 years (SD= 6.98). The overall prevalence of utilisation of clinic services was 708/874(81%) and 662/874(76%) reported satisfaction with the clinic services. Forty percent reported poor accessibility to the clinic, and of these 222/324 (69%) reported high transport-costs challenges. All women (100%) knew their HIV status, of these 463(53%) were HIV positive, of whom 455/463(98%) were receiving ART. Seventy six percent had been treated for STIs in the last three months, and 454(52%) reported partner violence. In the adjusted analysis, utilization of clinic services was more likely among HIV positive women (aRR=1.19; 95%CI: 1.11–1.28) and those who had been treated for STIs in the last three months (aRR= 1.32; 95%CI: 1.18–1.48). Conclusion: Prevalence for utilisation of clinic services was relatively high. Those who utilised the clinic were more likely to be HIV positive women and those treated for STIs. However, interventions targeting FSW to improve utilisation of HIV care services should be considered. Disclosure: No significant relationships.